Evolution and consistency in EU's energy security policy: analyzing the projects of common interest - Valdés, Javier (Papeles de Europa, 2016)
This article aims to contribute to the debate on the Projects of Common Interest (PCI) role in the EU’s energy security strategy. To accomplish that, the article frames the EU’s energy security strategy from an historical perspective. From a critical analysis of the PCI’s characteristics, it is analyzed the level of consistence and coherence with the main energy policy targets. Through this analysis special attention is devoted to their role in the development of the common energy markets. The study highlights the risk associated to the current disparity of interests among member countries and the lack of coherence with other energy policy targets. Furthermore, the study signals the necessity of reinforcing the development of physical infrastructure with a genuine governance in order to increase the homogenization of regulation and the development of a coordinated external and internal energy policy.
Keywords: energy policy; security; European Union; Energy Union; Projects of Common Interest